Дом без выхода: [роман] / Олег Рой - Рой Олег Юрьевич (Капризы судьбы, 2009)
10-11кл Экземпляры: Аб (20120323) / Инвентарный номер: 98371 / Цена: 60.00 / Авт.знак: Р 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6